Book Review: Hani S. Mahmassani (Ed.) In Perpetual Motion. Travel behaviour research opportunities and application challenges - Orfeuil, Jean-Pierre (European Journal of Transport and Infrastructure Research, 2002)
This book is based on the Eighth meeting of the International Association for Travel Behavior Research, held in Austin, Texas, in September 1997. IATBR is an active and joined together community2 focused on the improvement of methods aimed at measuring, representing, modelling and forecasting travel behaviour. This community developed in the seventies in reaction to aggregate models and their caveats. In that period, an impetus has been given in three directions: disaggregate approaches, with the project to capture the essence of individual rationality through more and more sophiticated models based on revealed or stated preferences; activity-based approaches, which have clearly demonstrated that analysing travel demand needs to go from trip-based approaches to tour-based and day-based approaches and put on the agenda such questions as the interrelations among persons (of a common household), the need to consider in-home as well as out-of-home activities and to improve dramatically the methods of data collection and mobility measurement; dynamic approaches, with a central message that the focus of the analysis should shift from the state of behaviour to changes in behaviour, with a specific attention to the speed of adjustments; If the three of them have now joined the same community, the book deals only at the margin with the second direction, the dynamic approach, even though a section is devoted to very short term behavioural response in the framework of ITS developments. This association acts as a home for dissemination and cross fertilization of ideas produced in the field of travel behavior by such disciplines as economics, psychology, sociology, urban planning, geography and transport engineeering. This position ‘across the boundary lines’ is reflected in the diversity of the areas of interest. Reviewing a six-hundred page, twenty-eight chapter book is always a hard task, not only because choosing between themes and authors is difficult and necessarily unfair, but because the book may also have different audiences, with different interests. Let’s consider, in that respect, what this book is not, and what this book is dealing with.